A higher TyG index is related with a higher prevalence of erectile dysfunction in males between the ages 20-70 in the United States, according to a cross-sectional research - Li, Lin; Yao, Hui; Dai, Wei; Chen, Yan; Liu, Heqian; Ding, Wei; Liu, Yingqing; Tao, Lingsong; Wang, Jiawei; Chen, Mingwei (Frontiers in Endocrinology, 2022)
Objective：This study aims to investigate the relationship between triglyceride glucose index (TyG) and erectile dysfunction (ED) among United States (US) adult males. Methods：A logistic regression analysis, subgroup analysis, and the computation of the dose-response curve were used to investigate the relationship between TyG index and ED prevalence among participants from the 2001-2004 National Health and Nutrition Examination Survey (NHANES) database. Results：After adjusting for all confounders, each unit increase in TyR index was associated with a 25 percent increase in ED prevalence (OR=1.25, 95 %CI:1.03, 1.52), and stratified analysis showed that elevated TyG index was associated with increased ED prevalence in the 50-year old group (OR=1.35, 95 % CI:1.05, 1.74), the Mexican-American group (OR=1.50, 95 % CI:1.00, 2.23) and BMI 25-29.9 kg/m2 (OR=1.48, 95 % CI:1.08, 2.01). The dose-response curve demonstrated a positive linear connection between the TyG index and the risk of ED. Conclusion: It has been shown that a higher TyG index is associated with a higher prevalence of erectile dysfunction, but no direct connection can be established.